The Actor in Search of Musical Forms. Case Studies - MILEA, Ada (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
This article looks at the major differences in the reception of the sounds of a musical fragment, depending on the personal experience of each individual and his profession. The musicians relate to the sound universe guided by the constituent elements of the scores, and the actors look for connections between sounds, gestures, words, characters, and stage situations. They can approach music in other ways than musicians and remember the melodic lines or create accompaniments by making connections with the context in which they find themselves. In some examples that the article offers, the studied actors demonstrate that sound can become music even in the absence of the vocal or rhythmic qualities of the performers. Other examples refer to the way in which the personality and creativity of artists have a significant role in creating songs or the sound support they need.